ESTUDO DO REGIME DE FLUXO SUBTERRÂNEO DA ÁREA DE INFLUÊNCIA DE UMA DESTILARIA DE ALCOOL EM CONCEIÇÃO DA BARRA - ES - Santos Júnior, Elias L. dos; Almeida, F. T. de; Alves, M. da G.; Tibana, S.; Zanotti, N. É. (Águas Subterrâneas, 2003)
Indisponível